Functional Changes of Mentalizing Network in SCA2 Patients: Novel Insights into Understanding the Social Cerebellum - Olivito, Giusy; Siciliano, L.; Clausi, S.; Lupo, M.; Romano, S.; Masciullo, M.; Molinari, M.; Cercignani, M.; Bozzali, M.; Leggio, M. (Cerebellum (London, England), 2020)
In recent years, increasing evidence of the cerebellar role in social cognition has emerged. The cerebellum has been shown to modulate cortical activity of social brain regions serving as a regulator of function-specific mentalizing and mirroring processes. In particular, a mentalizing area in the posterior cerebellum, specifically Crus II, is preferentially recruited for more complex and abstract forms of social processing, together with mentalizing cerebral areas including the dorsal medial prefrontal cortex (dmPFC), the temporo-parietal junction (TPJ), and the precuneus. In the present study, the network-based statistics approach was used to assess functional connectivity (FC) differences within this mentalizing cerebello-cerebral network associated with a specific cerebellar damage. To this aim, patients affected by spinocerebellar ataxia type 2 (SCA2), a neurodegenerative disease specifically affecting regions of the cerebellar cortex, and age-matched healthy subjects have been enrolled. The dmPFC, left and right TPJ, the precuneus, and the cerebellar Crus II were used as regions of interest to construct the mentalizing network to be analyzed and evaluate pairwise functional relations between them. When compared with controls, SCA2 patients showed altered internodal connectivity between dmPFC, left (L-) and right (R-) TPJ, and right posterior cerebellar Crus II. The present results indicate that FC changes affect a function-specific mentalizing network in patients affected by cerebellar damage. In particular, they allow to better clarify functional alteration mechanisms driven by the cerebellar damage associated with SCA2 suggesting that selective cortico-cerebellar functional disconnections may underlie patients’ social impairment in domain-specific complex and abstract forms of social functioning.